Physical Fitness Gymnastics Training for Improving the Quality of Physical Education Student - Nova, Andi; Syahputra, Muhajjir; Fitria, Fitria; Surimeirian, M Anas; Roberto, Julio; M, Benny Aprial; Nofrizal, Dedi; Tantri, Afri; Zati, Muhammad Rizqi (Universitas Lambung Mangkurat, 2025)
Increasing the competence of graduates is one of the Merdeka campus programs contained in key performance indicators 1 and 2, namely obtaining decent work and experience outside the campus. Preparing the competence of graduates, the Physical Education study program conducts physical fitness gymnastics training in collaboration with the Aceh Provincial Dispora. The activity was carried out for three days at the Multipurpose Building of Universitas Samudra, from February 1 to 3, 2024. The method of implementing activities uses participatory Action Research (PAR) with five stages: Planning, Implementation, Analysis, Action, and Sustainability. Activities include initial tests, material submission, practice tests, evaluations, and recommendations. There were 30 participants in physical education at FKIP Universitas Samudra semester IV. The assessment results of the guide resource persons showed that 13 categories were excellent, 14 were good, and three were in the sufficient category. Participants with good categories totalling 13 people are recommended to become trainers in campus environments, gymnastics studios in Langsa City, and government and private institutions.